If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 6x + 3 Reorder the terms: 9 + 3x = 6x + 3 Reorder the terms: 9 + 3x = 3 + 6x Solving 9 + 3x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 9 + 3x + -6x = 3 + 6x + -6x Combine like terms: 3x + -6x = -3x 9 + -3x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 9 + -3x = 3 + 0 9 + -3x = 3 Add '-9' to each side of the equation. 9 + -9 + -3x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 3 + -9 -3x = 3 + -9 Combine like terms: 3 + -9 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| 9t^2-t-8=0 | | 2x+3=4x+3 | | 16=b-22 | | 10-4(p+7)=2 | | 3x+2=-4x-75 | | 4y=45-y | | 2w^2+15w+28=0 | | 3x+3=-77-7x | | r(r+11)-42=0 | | Y-12=102 | | r^2+12r+27=0 | | r(r+5)-84=0 | | 6x+3x+2=83 | | 0.2c+4=6 | | r^2+11r-42=0 | | 2n=100 | | 5w^2+28w+32=0 | | -8+y=17 | | t^2+9t+18=0 | | 6g-3.5=8.5 | | 11p+2=2(p-8) | | -4m-9=-26.6 | | 30-42y=18 | | 448-3y=448 | | 4x-3y=448 | | 8x+8(x+2)=64 | | 24g^2-g-10=0 | | 3y+4x=448 | | 12p^2-4p+5=0 | | 7(2n+5)-2(4n+3)+5=4n | | 7(1-2n)+2(4n+3)+5=6n | | s^2=32-4s |